Atlas of Dark Destinations—Explore the World of Dark Tourism by Peter Hohenhaus - Stone, Philip R. (Journal of Scientific Exploration, 2022)
Dark tourism is an appellation defining travel to a diverse array of tourist sites that portray death, disasters, or calamities. For over 25 years, dark tourism as an international subject of scholarly interest has drawn together multidisciplinary discourse, where the dominion of the dead collides with contemporary touristic consumption. In turn, dark tourism has opened scholarly scrutiny of our significant Other dead and how societies deal with difficult heritage. Consequently, dark tourism is about polysemic touristic encounters with our memorialized dead, where a fine line exists between commemoration and commercialism. Dark tourism is inherently political and dissonant, as (re)presentations of our dead are imbued with sociopolitical bias and where remembrance is politically engineered and hegemonically orchestrated. Whereas heritage may produce narratives for dark tourism, it is the tourist experience that consumes such messages and co-constructs meaning making. Indeed, dark tourism displays our fights, follies, failures, and misfortunes, and subsequent tourist experiences of our ‘heritage that hurts’ mediates a sense of mortality at places of fatality.